Implementasi Isi Kandungan Surat Al’maun dalam Membentuk Karakteristik Sosial Peserta Didik di SDN Grogor Selatan 09 - Suherman Jaksa; Dhinul Habdi; Yunan Adham; Lilik Umami; Nurmalia Lusida; Andriyani Andriyani (Moral : Jurnal kajian Pendidikan Islam, 2025)
Islam teaches that if there is an interest or need, it is recommended to spend wealth to donate. Infaq is an act of worship that is sunnah. Donation activities have two benefits, namely to meet the basic needs of the poor and help them to carry out good deeds. Islam has taught its followers that they have an obligation to help each other, especially those who are weak (the Dhuafa), the poor, and those in need. The aim of this research is the implementation of Surah Al-Ma'un values ​​education in shaping the social character of students at SDN Grogol Selatan 09 South Jakarta. This research method uses descriptive curative with a field research approach. Data collection techniques use observation, interviews and questionnaires. The population in this study was Islamic religious teachers and grade 5 and grade 6 students. The sample for this research was 30 people. Based on the research results, social interaction activities such as infaq activities carried out at SDN Grogol Selatan 09 can have an influence and impact on the social care character of students. With this habituation, students are able to develop values, attitudes and behavior that can radiate morals or character. The most important thing is that the key to changing the younger generation for the better is social character education, so that it can ensure that students have good character and personality in the future.